Measurement Invariance of the Brief Multidimensional Student's Life Satisfaction Scale Among Adolescents and Emerging Adults Across 23 Cultural Contexts. (February 2016) - Abubakar, Amina; van de Vijver, Fons; Alonso-Arbiol, Itziar; He, Jia; Adams, Byron; Aldhafri, Said; Aydinli-Karakulak, Arzu; Arasa, Josephine; Boer, Diana; Celenk, Ozgur; Dimitrova, Radosveta; Ferreira, Maria Cristina; et al.
There is hardly any cross-cultural research on the measurement invariance of the Brief Multidimensional Students' Life Satisfaction Scales (BMSLSS). The current article evaluates the measurement invariance of the BMSLSS across cultural contexts. This cross-sectional study sampled 7, 739 adolescents and emerging adults in 23 countries. A multi-group confirmatory factor analysis showed a good fit of configural and partial measurement weights invariance models, indicating similar patterns and strengths in factor loading for both adolescents and emerging adults across various countries. We found insufficient evidence for scalar invariance in both the adolescents' and the emerging adults' samples. A multi-level confirmatory factor analysis indicated configural invariance of the structure at country and individual level. Internal consistency, evaluated by alpha and omega coefficients per country, yielded acceptable results. The translated BMSLSS across different cultural contexts presents good psychometric characteristics similar to what has been reported in the original scale, though scalar invariance remains problematic. Our results indicate that the BMSLSS forms a brief measure of life satisfaction, which has accrued substantial evidence of construct validity, thus suitable for use in cross-cultural surveys with adolescents and emerging adults, although evaluation of degree of invariance must be carried out to ensure its suitability for mean comparisons.